DEVELOPMENT OF MACROSCOPIC TRAFFIC FLOW MODELS FOR URBAN ROADS - AJIBADE, MATHEW KAYODE (2023)
Availability of adequate mathematical models for vehicular traffic is a pre-requisite for the development of efficient traffic control strategies. Macroscopic traffic flow models, that is, speed-flow-density relationships, are the most useful tools in highway design and planning process. They are useful in predicting the roadway capacity, determining the adequate level-of-service of traffic flow and travel time for a given roadway. The challenge faced by urban traffic in both developed and developing countries is infrastructure deficiency. Consequently, vehicular traffic volume has rapidly outstripped the capacity of the nation’s roadways. It has therefore become increasingly necessary to understand the dynamics of traffic flow and obtain mathematical description of the processes in order to address this problem; hence, this study. Traffic flow data (traffic volume and travel speed) were collected along Post Office – Obafemi Awolowo Teaching Hospital Complex Road in Ile-Ife during the morning and evening peaks using the manual technique at an interval of 15-minutes for seven days. Traffic density was computed using the fundamental traffic flow equation. Speed-density model was thereafter developed using linear regression technique. Flow-speed and flow-density models were then developed from the speed-density model by applying the fundamental traffic flow relationship. Traffic parameters deduced from these models were then used to assess the performance of the road. The results obtained showed that the traffic flow data collected was composed of 23 % passenger cars, 25 % buses, 2 % trucks and 50 % motorcycles. The speed-density, flow-speed and flow-density models were U_s=-0.324K+41.13, Q=-3.09〖U_s〗^2+126.94U_s, and Q=-0.324K^2+41.13K, respectively. R2 values of 0.611, 0.942, and 0.431 for speed-density model, flow-speed model, and flow density model, respectively. A free flow speed (Us) of 41.16 km/h, optimum speed (Uo) of 20.57 km/h, jam density (Kj) of 126.94 pc/km/ln, optimum density (Ko) of 63.5 pc/km/ln, percentage free flow speed (PFFS) of 50.10% , level of service E, traffic capacity (C) of 1306 pc/h/ln (which was found less than the required traffic capacity of 1500 pc/hr/ln for an urban two-way two-lane highway), were obtained for this study. In conclusion, this study provided a new means of determining the level of service and performance rating of two-lane highways compared to the method provided in the Highway Capacity Manual (HCM). Traffic parameters obtained from this study showed that the road is operating below the required capacity and at the level of service E. This denotes that the capacity of the highway has been reached. And that traffic ﬂow conditions are best described as unstable with any traffic incident causing extensive queuing and even breakdown. Levels of comfort and convenience are very poor and travel speeds are low. Hence, timely effective traffic management plan for urban roads is recommended in order to withstand the increasing travel demand.